School as an Arena of Social Reproduction: A Phenomenological Study of Private Elementary Schools in Wonosari, Klaten - Nur’aini Inayah; Eufrasia Kartika Hanindraputri; Wardatul Adawiyah; Arief Sudrajat; Yuanita Dwi Hapsari (Faculty of Social Science, Universitas Negeri Malang, 2024)
Primary education is considered a means of instilling basic values for children. It is no wonder that parents are often selective in choosing primary schools for their children. This study tries to describe the rationality of parents sending their children to private Islamic-based primary schools. Data collection techniques were conducted by observation and interview. Researchers conducted interviews with parents of students and the school. The main subjects in this study were parents of students at SD Negeri Wonosari District and SDIT Ar-Risalah, totaling 10 people. The selection of informants was carried out using the porpusive sampling technique. The results of interviews and observations were triangulated to find the truth of the data found. Then the data was analyzed using Pierre Bourdieu's social reproduction theory. The results obtained that private schools are quite attractive to parents because the services and facilities they provide are quite adequate. This is seen as providing opportunities for success for their children. In addition, the habitus instilled by private elementary schools is considered symbolic capital and can determine student behavior. Through a habitus that is in accordance with the standards of parents in the upper class, it will form habits and determine the social class for their children. These services and facilities are inversely proportional to public elementary schools that have not been able to keep up with private elementary schools. This has led to a decline in the existence of public elementary schools in the society.